Mentoring in the Preparation of Literacy and GEDSI Based Teaching Modules - Delora Jantung Amelia; Abdurrohman Muzakki; Roslinawati Roslan (Jurnal Pemberdayaan Masyarakat, 2025)
Based on the results of interviews and field observations, the issues faced by SDN Gadingkulon 2 in Malang Regency are as follows: Teachers still face difficulties in implementing literacy in classroom learning activities. The school has already implemented a literacy movement but has not yet integrated literacy into the learning activities. Teachers need to develop a literacy concept that can integrate literacy-based learning activities. Some students in the learning activities have diverse academic abilities. The methods used in this empowerment activity begin with a workshop on mentoring the creation of literacy and GEDSI-based teaching modules, mentoring in module preparation, module implementation, and reflection and follow-up. The results of this mentoring activity have had an impact on the participants, including successfully enhancing the teachers' skills in developing teaching modules that integrate literacy and GEDSI values. The teachers were also able to utilize artificial intelligence technology, ChatGPT, to enrich the content of the teaching modules. The modules developed cover various subjects, leveraging ChatGPT to search for references and creative ideas in module preparation. Students can understand true literacy, which is not just about reading sentences without understanding the meaning contained in each sentence, so that it can be applied and implemented in daily activities.